Hubungan Fisiologis Indeks Massa Tubuh dan Kenaikan Berat Badan Ibu Hamil dengan Resiko Preeklampsia - Yuni Kurniati; Yuli Bahriah (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
Preeclampsia is a hypertensive disorder that occurs specifically during pregnancy, usually occurring after 20 weeks of gestation. Preeclampsia is characterized by high blood pressure (hypertension) and the presence of protein in the urine (proteinuria). This study aims to analyze the relationship between physiological Body Mass Index and maternal weight gain on the risk of preeclampsia. The method used is an analytical observational with a case-control approach. The sample obtained was 40 for the control group and 40 for the case group. The results of the bivariate analysis test regarding the relationship between maternal BMI and the risk of preeclampsia obtained a p value of 0.000 < α = 0.05, this means there is a significant relationship between maternal BMI and the risk of preeclampsia. Based on the results of the statistical analysis, an Odds Ratio (OR) value of 2.945 was obtained, indicating that the group with a high Body Mass Index (BMI) has a 2.945 times greater chance of experiencing preeclampsia than the control group. This finding is supported by a p-value of 0.000, proving a statistically significant association between maternal weight gain during pregnancy and the risk of preeclampsia. Furthermore, an OR of 6.782 was obtained, indicating that the group with high weight gain during pregnancy had a 6.782-fold higher risk of developing preeclampsia. In conclusion, there is a significant association between physiological Body Mass Index (BMI) and maternal weight gain during pregnancy and the risk of preeclampsia..